a(11)=2-6(11-1)

Simple and best practice solution for a(11)=2-6(11-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a(11)=2-6(11-1) equation:


Simplifying
a(11) = 2 + -6(11 + -1)

Reorder the terms for easier multiplication:
11a = 2 + -6(11 + -1)

Combine like terms: 11 + -1 = 10
11a = 2 + -6(10)

Multiply -6 * 10
11a = 2 + -60

Combine like terms: 2 + -60 = -58
11a = -58

Solving
11a = -58

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '11'.
a = -5.272727273

Simplifying
a = -5.272727273

See similar equations:

| x+(.08x)=18.90 | | k/2=2 | | 8x-6x^2-8=0 | | X^6-37=0 | | 8x-6=5x-4.5 | | 11.20x+10.20y=428 | | X^4+x^2-2= | | w-11=2 | | 6y-x+7=0 | | 12a-2(5a-4)= | | 13=-4d | | 8x-41=180 | | -45-3v=-66 | | -7/10=x/10 | | 5x(3x+9)=0 | | 8x+41=180 | | 16/3=m/3 | | c-14=5 | | 7x=4y-5 | | -9=n+6 | | 3=j/3 | | 6=3h | | .3h=15 | | 27-8p=123 | | 27-8p=23 | | 15x+14=18x+5 | | r-1=5 | | 26-8p=123 | | 18a-10=8a+20 | | 10y=3y+7 | | 20c+14=19c+17 | | 17y-9=18y-13 |

Equations solver categories